Enhancing Understanding of Momentum and Impulse Concepts through a Video-Assisted Problem-Based Learning Model - Nining Fitriani; Sutrio Sutrio; Gunawan Gunawan (Indonesian Publication Center, 2024)
This study examines the effect of a video-assisted problem-based learning (PBL) model on enhancing students' understanding of momentum and impulse concepts. The research involved all class X MIPA students from a Madrasah Aliyah (MA) in East Lombok. Purposive sampling was employed to select class X MIPA 1 as the experimental group and class X MIPA 2 as the control group. A nonequivalent control group design was utilized, with the experimental group receiving video-assisted PBL instruction and the control group receiving conventional learning. Seven indicators were used to measure concept understanding through a nine-item essay test. Data analysis using a polled variance t-test revealed that the video-assisted PBL model significantly improved students' understanding of momentum and impulse concepts.